A Li K‐edge XANES study of salts and minerals. (21st February 2018) - O'Shaughnessy, Cedrick; Henderson, Grant S.; Moulton, Benjamin J. A.; Zuin, Lucia; Neuville, Daniel R.
Abstract : The first experimental results at the Li K ‐edge of a variety of silicate and phosphate minerals are presented. The results are interpreted using information gained from simple Li‐bearing salt compounds. The ionicity of the Li—O bond can be estimated using the presence of a weak edge feature as observed in Li metal. Abstract : The first comprehensive Li K ‐edge XANES study of a varied suite of Li‐bearing minerals is presented. Drastic changes in the bonding environment for lithium are demonstrated and this can be monitored using the position and intensity of the main Li K ‐absorption edge. The complex silicates confirm the assignment of the absorption edge to be a convolution of triply degenerate p ‐like states as previously proposed for simple lithium compounds. The Li K ‐edge position depends on the electronegativity of the element to which it is bound. The intensity of the first peak varies depending on the existence of a 2 p electron and can be used to evaluate the degree of ionicity of the bond. The presence of a 2 p electron results in a weak first‐peak intensity. The maximum intensity of the absorption edge shifts to lower energy with increasing SiO2 content for the lithium aluminosilicate minerals. The bond length distortion of the lithium aluminosilicates decreases with increasing SiO2 content, thus increased distortion leads to an increase in edge energy which measures lithium's electron affinity.